The Balance Between Corporate Identity And Corporate Image And Its Impact On Marketing Of Universities In Ghana - Boafo, Nana Danso; Agyapong, Fred; Asare, Priscilla; Amponsah, Grace (Archives of Business Research, 2020)
Universities are adopting different strategies to attract students, enhance satisfaction level and loyalty as well as branding in a competitive market. Although university corporate identity and image is becoming an increasingly important issue in the marketing of universities in Ghana, there is sometimes a mismatch between the university corporate identity and image which can lead to poor marketing performance. This has therefore necessitated this study which is, evaluating the balance between corporate identity and corporate image and its impact on marketing performance of universities in Ghana using Christian Service University College as the case study. The study was descriptive. Population was past and current students of the university. Five hundred and seventy five (575) persons were sampled using convenience sampling method. Multiple linear regression was used to analyze data. Findings revealed a balance between CSUC corporate identity and corporate image, as it has positively impacted on the university’s marketing performance in these challenging times for private universities in Ghana. This was based on the evidence that, majority of the responses attested to the fact that the university practiced its Christian values inbuilt in its brand , also the university does what it says it stands for. Respondents were happy with lecturers and the university graduates’ performances on the field. The study recommended that Universities must create a perfect fit between their corporate identity and corporate image since they impact on their marketing performance, and also all staff must be made to understand the relationship between the institution’s corporate identity and corporate image and its impact on marketing performance of the institution.